Risk leaving gaps? Vaccination status of employees in occupational healthcare screening Mut zur Lücke? Impfstatus von Beschäftigten in der arbeitsmedizinischen Vorsorge - Jungbluth, Michael; Otte, Nelly; Kaifie, Andrea; Kraus, Thomas; Krabbe, Julia (Zentralblatt für Arbeitsmedizin, Arbeitsschutz und Ergonomie, 2024)
Introduction: Comprehensive surveys have shown a vaccination gap for all recommended vaccinations for adults in Germany. Occupational physicians could close this gap as part of occupational health screening. Methods: The medical vaccination records of 5999 occupational medical examinations were retrospectively analyzed. The vaccination rates for tetanus, diphtheria, poliomyelitis, pertussis and measles were analyzed for 1126 employees with an occupational medical screening for activities with biological substances (infection hazard) and 184 employees with other reasons for occupational physician visits. Gender, age, economic sector and socioeconomic position (SEP) were recorded as possible influencing factors. Results: The analysis of 1310 employees from 47 companies showed a vaccination gap for standard vaccinations in 73.1%. The reason for an occupational physician visit had no influence on the vaccination rates. The vaccination rate in the vaccination certificate was influenced by gender and economic sector for tetanus and predominantly by age for measles. The socioeconomic position had no direct influence on vaccination status. Overall, a need for further vaccinations was identified for all standard vaccinations. Discussion: Based on the vaccination certificate there was a significant vaccination gap that could be closed in an occupational health setting, independent of the reason for the medical visit. Every contact with an occupational physician should be used for this purpose. As there was evidence of incomplete documentation of vaccinations that had already been carried out, the effort for an electronic documentation seems to be worthwhile to be able to validly and completely record the immune status and through this the need for vaccination. In combination with cross-sector accessibility, unnecessary vaccinations could also be avoided.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Occupational health screening; Vaccination; Vaccination gap; Vaccination prevention; Vaccination rate